Inovasi Model Pembelajaran Bimbingan Membaca Kitab Dalam Menghadapi Mahasiswa Multikultural - Najib Ihsan (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2026)
The model of learning to read classical Islamic texts is an important component in the learning process, and it is hoped that this method will support the continuity of learning. The purpose of this study is to develop and analyze a model of learning to read classical Islamic texts that can be adapted to the needs of multicultural students. This study used a qualitative method with a case study approach. Data were obtained from observations, interviews, and documentation studies on the process of reading guidance in religious universities. The results showed that a learning model that combines the use of digital media, collaboration, and differentiation can increase student participation, understanding, and motivation. In addition, it has been proven that a culture-based learning approach creates an inclusive and dialogical learning environment. This study found that the development of a new scripture reading guidance model not only strengthens students' academic abilities but also makes them more familiar with other cultures while learning. This study is expected to be a reference for educators in developing educational methods that are responsive to the heterogeneity of their students.